DIPLOMASI PUBLIK INDONESIA DALAM MEMPROMOSIKAN PARIWISATA DI MALAYSIA MELALUI WONDERFUL INDONESIA PERIODE 2015-2019 - Muhammad Ivan Adiyatma Suhartono (2021)
This study describes Indonesia's public diplomacy efforts in promoting tourism in Malaysia through Wonderful Indonesia during the 2015-2019 period. Where this is done in order to attract foreign tourists from Malaysia to come to visit Indonesia. This study raised the research, namely "How are Indonesia's Public Diplomacy Efforts in Promoting Tourism in Malaysia Through Wonderful Indonesia Throughout 2015-2019?". To answer this question, the researcher uses the concepts of bilateral cooperation, public diplomacy, multi-track diplomacy, and tourism. The results show that Indonesia's public diplomacy efforts are actually quite good, especially those carried out by state actors. State actors also cooperate with non-state actors to work hand in hand in promoting Indonesian tourism in Malaysia. All activities carried out by the Indonesian side are aimed at disseminating culture and relations with the Malaysian community in order to create a positive image and reputation of Indonesian tourism. However, the use of Malaysian local media and the activeness of Indonesian non-state actors to act independently without being co-opted by state actors created a gap in Indonesia's public diplomacy efforts to promote tourism in Malaysia.